Influence of metabolic profile on macro- and microvascular damage in patients with moderate, high and very high cardiovascular risk - E. K. Serezhina; A. A. Obrezan; A. G. Obrezan (Российский кардиологический журнал)
Aim. To evaluate the association of the triglyceride-glucose index (TGI) with micro- and macrovascular changes in patients with moderate, high and very high cardiovascular risk (CVR).Material and methods. The study included 134 men and 129 women aged 40 to 65 years with a SCORE2 ten-year risk of adverse cardiovascular events of 2,5% or more. Based on a detailed survey, a comprehensive physical and paraclinical examination, the relationship between TGI and CVR factors was assessed using Pearson correlation analysis, followed by a linear correlation strength assessment using the Chaddock scale. Modeling of the TGI association with macro- and microvascular damage in patients with moderate CVD was performed using multivariate logistic regression.Results. According to regression analysis, increased TGI was associated with an increased risk of both macrovascular and microvascular changes. Similar results were obtained using multivariate logistic regression with model adjustment for age, sex, body mass index, waist circumference, smoking, hypertension, family history of premature cardiovascular disease, lipid-lowering therapy, and glucose-lowering therapy. An increased level of TGI was associated with an increase in the odds ratio (OR) of carotid atherosclerosis (OR 1,73, 95% confidence interval 1,27-2,36, P for trend <0,001), an increase in the urine albumin-creatinine ratio (OR 1,61, 95% CI 1,22-2,13, P for trend <0,001) and a decrease in estimated glomerular filtration rate (OR 1,67, 95% CI 1,10-1,50, P for trend =0,02).Conclusion. TGI is an important and accessible additional risk factor for both micro- and macrovascular damage in everyday clinical practice, regardless of whether the patient has diabetes. For personalized CVR stratification and determination of further management tactics for patients with moderate, high and very high CR, the maximum available factors should be assessed, each of which can influence the disease course, while the summation of the main and additional factors significantly worsens the prognosis.